ESG Ratings and Firms’ Access to Finance: An International Perspective - Bhatti, Shahbaz ul Hassan; Khattak, Mudeer Ahmed (Journal of Development and Social Sciences, 2025)
This study investigates the impact of sustainability ratings on financial constraints among banks and other financial institutions using global data from 2010–2023. Integrating ESG into business models is crucial for sustainable development due to mounting regulatory pressures and responsible investors’ choices to direct funds towards responsible firms. The sustainable practices of financial institutions have implications not only for global environmental concerns but also for social and governance domains, which are inextricably interconnected. While existing research has focused on ESG ratings and financial performance, the specific connection between ESG and financial constraints has received limited attention. Given the intertwined nature of sustainability goals and financial implications, this study investigates the impact of sustainability ratings on financial constraints among banks. The study employs panel data regressions to analyze the relationship between ESG ratings and financial constraints A sub-sample analysis is also conducted to compare the effects between developed and developing economies. The findings reveal that an aggressive sustainability strategy results in lower financial constraints. The results are robust to alternative proxies of financial constraints and alternative regression estimators. This research provides a compelling case and a substantive argument for financial organizations to prioritize corporate sustainability considerations in their decision-making process.